1975
DOI: 10.1128/iai.12.2.437-439.1975
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes infection in nude mice

Abstract: As compared to phenotypically normal (nu/+)NMRI mice showing the typical course of an experimental listeric infection, that of congenitally hypothymic (nude, nu/nu)NMRI mice was found to be characterized from the outset bya chronic trend. During the early phase of the infection, significantly reduced numbers of Listeria monocytogenes were observed in the spleens of nude mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
37
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 8 publications
6
37
0
Order By: Relevance
“…However, in addition to the specific defense mechanism, there appears to exist a nonspecific defense mechanism that mainly acts as an effector ofresistance during the early phase of infection, before specifically sensitized T lymphocytes and macrophages activated by T cells contribute to defense. This agrees with findings that thymusless mice do not succumb to infection with L. monocytogenes or Brucella abortus within a few days (2,4). The increased resistance of nude mice during the initial phase of infection as compared with that of euthymic mice is evidently due to the fact that their macrophages are continuously stimulated by bacteria invading permanently through the immune-deficient wall ofthe intestine (13).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, in addition to the specific defense mechanism, there appears to exist a nonspecific defense mechanism that mainly acts as an effector ofresistance during the early phase of infection, before specifically sensitized T lymphocytes and macrophages activated by T cells contribute to defense. This agrees with findings that thymusless mice do not succumb to infection with L. monocytogenes or Brucella abortus within a few days (2,4). The increased resistance of nude mice during the initial phase of infection as compared with that of euthymic mice is evidently due to the fact that their macrophages are continuously stimulated by bacteria invading permanently through the immune-deficient wall ofthe intestine (13).…”
Section: Discussionsupporting
confidence: 90%
“…The development of those effector cells is commonly considered to rest upon the release of a nonspecific signal by sensitized T cells, resulting in the production of activated macrophages (17). Surprisingly, nude mice with congenital dysplasia of the thymus and complete lack of T lymphocytes have recently been found to possess an enhanced bactericidal activity for L. monocytogenes during the initial phase of experimentally produced listeric infections (2,4). However, in contrast to phenotypically normal control animals, nude mice are not able to effectively control and terminate infection by L. monocytogenes (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, bacterial loads in the early stages of infection were from 4 to 130-fold lower in 5aV/versus C.B-17 mice. Similar chronic infection has also been observed in athymic nude mice (Emmerling et al 1975, Cheers & Waller 1975, Nickol & Bonventre 1977 and following depletion of CD4 and CD8 T cells in immunocompetent mice (Sasaki et al 1990). Thus, in the absence of antigen-specific immunity, T cell-independent processes partially controlled replication of Listeria in vivo.…”
Section: Macrophage Activation During Infection Of Scid Micesupporting
confidence: 62%
“…These data are in agreement with the observations of Zinkernagel and Blanden (29), who found that the elimination of L. monocytogenes from the tissue of thymectomized mice was impaired from days 3 to 6 of infection. Similarly, Emmerling et al (9,10) found that nude mice showed increased resistance to L. monocytogenes during the initial phase of infection, but this was followed by continued infection with a chronic trend not seen in normal mice.…”
Section: Resultsmentioning
confidence: 89%